Total Synthesis of Putative Chagosensine. Issue 41 (17th September 2018) - Heinrich, Marc; Murphy, John J.; Ilg, Marina K.; Letort, Aurélien; Flasz, Jakub; Philipps, Petra; Fürstner, Alois
Abstract: The marine macrolide chagosensine is the only natural product known to date that embodies a Z, Z ‐configured chloro‐1, 3‐diene unit. This distinguishing substructure was prepared by a sequence of palladium‐catalyzed 1, 2‐distannation of an alkyne precursor, regioselective Stille cross‐coupling at the terminus of the resulting bisstannyl alkene with an elaborated alkenyl iodide, followed by chloro‐destannation of the remaining internal site. The preparation of the required substrates centered on cobalt‐catalyzed oxidative cyclization reactions of hydroxylated olefin precursors, which allowed the 2, 5‐ trans ‐disubstituted tetrahydrofuran rings, embedded into each building block, to be formed with excellent selectivity. The highly strained macrolactone could ultimately be closed under forcing Yamaguchi conditions. Comparison of the spectral data of the synthetic sample with those of authentic chagosensine methyl ester confirmed that the structure of this intriguing compound has been mis‐assigned by the isolation team. Abstract : Unique : Chagosensine is the only natural product known to date comprising a Z, Z ‐configured chloro‐1, 3‐diene unit. This distinguishing motif was obtained by serial alkyne 1, 2‐distannation, regioselective Stille coupling and chloro‐destannation. The recorded spectral data showed, however, that the stereostructure of this marine macrolide had been mis‐assigned by the isolation team.